VD_FINDINFO Jug / 2024 / 238 vom 20. Dezember 2023 - VD Tribunal cantonal (2023)
ASSASSINAT, TENTATIVEDROIT PÉNAL, REJET DE LA DEMANDE, PRÉSOMPTION D'INNOCENCE | 139 ch. 1 CP, 181 CP, 22 ad 112 CP, 239 CP, 291 CP, 19a ch. 1 LStup